Effect of Rapid Two-Step Freezing on Bone Marrow Cell Integrity - Ostankov, M. V. (Problems of Cryobiology and Cryomedicine, 2007)
Supercooling of murine bone marrow intracellular solution under cell suspension cooling with a constant rate and at a rapid twostep freezing has been theoretically calculated. The optimal conditions for these cells cryopreservation under dimethyl sulfoxide protection have been determined, basing on the calculations and experiments performed.